ESTIMATION OF AIRCRAFT ACCIDENT RISK IN CONTROLLER RESPONSIBILITY ZONE AIRSPACE WHILE PROVIDING AIRCAFT SERVICE WITH ATM SURVEILANCE SYSTEM DATA - V. B. Spryskov; K. L. Isaakian; S. V. Kuzntesov (Научный вестник МГТУ ГА, 2016)
The article describes the models for assessing aircraft accident risk due to aircraft coordinate information errors at the controller’s air situation display. The models allow to justify safety requirements on aircraft coordinates display accuracy or to assess the current aircraft accident risk by analyzing observed intervals between aircraft and parameters of the surveillance system.